PERJANJIAN MALINO SEBAGAI HASIL DARI UPAYA MEDIASI KONFLIK DI KONFLIK MALUKU - Sajiwo, Bagus Budi (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2022)
Conflict can be interpreted as conflict, dispute, or conditions that are not in accordance with what they should be, conflict is usually accompanied by violence, but it is undeniable that there are conflicts that are not accompanied by violence. In Indonesia, conflict is not something new, it even occurs relatively often, this is because Indonesia is a pluralistic/multicultural country, with that difference Indonesia is prone to conflict. Like the conflict in Maluku in 1999. After the outbreak of the reformation event, it provided an opportunity for certain groups in Maluku to vent their grudges that had been buried so far. The Maluku conflict went on for a long time and claimed many lives. This study aims to find out how the Malino Agreement is an effort of conflict mediation in this complex Maluku conflict.